Performance of Intercropping Groundnut with Sesame (Bangladesh Agronomy Journal, 2017)
The experiment was carried out at the farmers’ field of On-Farm Research Division, Bangladesh Agricultural Research Institute (BARI), Mymensingh during two consecutive years 2015 and 2016 to find out the suitable intercropping system for increasing crop productivity and profitability of groundnut with sesame intercropping system. The treatments were T1=sole groundnut, T2=sole sesame, T3= Two rows of groundnut in between paired rows of sesame and T4= Three rows of groundnut in between paired rows of sesame. Treatments were arranged in a randomized complete block design with six dispersed replications. Between intercropped treatments, three rows of groundnut within paired rows of sesame showed higher sesame equivalent yield (2.33 tha-1) and groundnut equivalent yield (2.14 tha-1) which provided the yield advantages of 108 and 32% over the respective sole crops. The highest land equivalent ratio (1.64), gross return (Tk 1,28,350 ha-1) and benefit cost ratio (2.15) were also achieved in three rows of groundnut within paired rows of sesame compared to other intercropping and sole cropping systems. The result showed that three rows of groundnut in between paired rows of sesame is found most productive and profitable than sole sesame or sole groundnut for maximum profit in Mymensingh regionBangladesh Agron. J. 2017, 20(1): 99-105